Total bilirubin and bilirubin-to-triglycerides ratio predict changes in glycated hemoglobin in healthy children - Puerto-Carranza, Elsa; Nuevo-Casals, Silvia; Roca-Portella, Berta; Mas-Parés, Berta; Gómez-Vilarrubla, Ariadna; Carreras-Badosa, Gemma; Niubó, Maria; Prats-Puig, Anna; de Zegher, Francis; Ibáñez, Lourdes; Bassols, Judit; López-Bermejo, Abel (Frontiers in endocrinology (Lausanne), 2023)
Bilirubin and triglycerides can regulate insulin secretion and glucose uptake. The aim of our study is to analyze associations between total bilirubin (TB) and the bilirubin-to-triglycerides ratio (BTR) with metabolic markers in healthy prepubertal children. Subjects were 246 healthy children (mean age 8), of whom 142 (58%) were reevaluated 4 years later (mean age 12). The subjects were stratified according to age into three groups (<7.8 years; 7.8-9.6 years; and >9.6 years; n=82 each) at baseline and into two groups (<12.9 years and ≥12.9 years; n=71 each) at follow-up. Anthropometrics and laboratory parameters [TB and its fractions (direct and indirect bilirubin), triglycerides, HDL-cholesterol, glucose, insulin, HOMA-IR, HOMA-B and glycated hemoglobin (HbA1c)] were assessed at both baseline and follow-up. TB and BTR showed independent and negative association with baseline and follow-up HbA1c. These associations were stronger for BTR and in the highest age group. No independent associations were observed with HOMA-IR or HOMA-B. TB and BTR are independently associated with HbA1c and predict its changes over time in healthy children. Our results indicate that TB and BTR may be useful parameters in studies of glucose tolerance in healthy children.